Partisipasi Perempuan dalam Pembangunan Desa di Kecamatan Candi - Yunita Farah Monica; Luluk Fauziah (Universitas Muhammadiyah Sidoarjo, 2017)
This study aimed to describe women's participation in rural development and constraints of women's participation in rural development in Jambangan Village, Candi District, Sidoarjo Regency. This research used descriptive qualitative research method. The data used came from primary and secondary data. Informants were categorized into two that were key informant and informant. The techniques of data collection were observation, documentation and interview toward related parties; that werepublic figures community, especially women, village head, apparatuses and BPD. The result was the woman’s participationand involvement in planning and implementation of development in Jambangan were substantial even though there were no women in the organizational structure. The form of woman’s participation were mind, fund, vitality, self-help, etc. The participation included physical development, social activities, economics and religious. In evaluating and monitoring rural development, woman’s participation and involvement were not maximal yet even they had a means of complain in each sub region but until the day suggestion and critics were deficient. The obstacles of woman’s participation were time, fund, and self-knowledge of the woman.